Investigation of vortex behavior in the organic superconductor κ-(BEDT-TTF)2Cu(SCN)2 using muon spin rotation - Lee, S; Pratt, F; Blundell, S; Aegerter, C; Pattenden, P; Chow, K; Forgan, E; Sasaki, T; Hayes, W; Keller, H (1997)
Muon spin rotation (μSR) measurements have been performed on the organic superconductor κ-(BEDT-TTF)2Cu(SCN)2 in order to investigate its exotic vortex behavior. Previously unobserved features of the μSR line shapes have been measured at low fields and temperatures. In the mixed state the existence of a lattice composed of linear vortices is demonstrated at low fields. The breakup of this well-ordered lattice has furthermore been observed as a function of both field and temperature.